The Prevalence and Prognosis of Resistant Hypertension in Patients with Heart Failure - Jin, Chun-Na (PLoS One, 2014)
BACKGROUND: Resistant hypertension is associated with adverse clinical outcome in hypertensive patients. However, the prognostic significance of resistant hypertension in patients with heart failure remains uncertain. METHODS AND RESULTS: The 1 year survival and heart failure re-hospitalization rate of 1288 consecutive patients admitted to a university hospital for either newly diagnosed heart failure or an exacerbation of prior chronic heart failure was analyzed. Resistant hypertension was defined as uncontrolled blood pressure (>140/90 mmHg) despite being compliant with an antihypertensive regimen that includes 3 or more drugs (including a diuretic). A total of 176 (13.7%) heart failure patients had resistant hypertension. There was no difference in all cause mortality, cardiovascular mortality, and heart failure related re-hospitalization between patients with versus without resistant hypertension. Diabetes [hazard ratio = 1.62, 95% confidence interval = 1.13–2.34; P = 0.010] and serum sodium >139 mmol/L (hazard ratio = 1.54, 95% confidence interval = 1.06–2.23; P = 0.024) were independently associated with resistant hypertension. Patients with resistant hypertension had a relatively higher survival rate (86.9% vs. 83.8%), although the difference was not significant (log-rank x(2) = 1.00, P = 0.317). In patients with reduced ejection fraction, heart failure related re-hospitalization was significantly lower in patients with resistant hypertension (45.8% vs. 59.1%, P = 0.050). CONCLUSIONS: Resistant hypertension appears to be not associated with adverse clinical outcome in patients with heart failure, in fact may be a protective factor for reduced heart failure related re-hospitalization in patients with reduced ejection fraction.